2013
DOI: 10.1007/s10649-013-9470-x
|View full text |Cite
|
Sign up to set email alerts
|

Adult numeracy and the totally pedagogised society: PIAAC and other international surveys in the context of global educational policy on lifelong learning

Abstract: Copyright and moral rights to this thesis/research project are retained by the author and/or other copyright owners. The work is supplied on the understanding that any use for commercial gain is strictly forbidden. A copy may be downloaded for personal, non-commercial, research or study without prior permission and without charge. Any use of the thesis/research project for private study or research must be properly acknowledged with reference to the work's full bibliographic details.This thesis/research projec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 32 publications
(40 reference statements)
2
34
0
2
Order By: Relevance
“…The fields of ethnomathematics, critical mathematics education and, more generally, what have been known as the social, cultural and political perspectives in mathematics education have shown how mathematics is involved in processes of social selection, in excluding groups of people considered to be disadvantaged, or in providing a clear social mechanism of accountability and accreditation. A recent special issue on social theory published in this journal contemplates research where it is shown how mathematics is used as an economic measure (Tsatsaroni & Evans, 2013), a technology of subjectification (Kanes, Morgan & Tsatsaroni, in press) or as a mechanism of social selection (Jorgensen, Gates & Roper, 2013). These studies compel us to think about the importance of mathematics not in terms of object mathematicsas valuable knowledge and competencebut in terms of the role it plays and its attendant submissions to political as well as economic criteria and goals.…”
Section: Fetishism and Mathematicsmentioning
confidence: 99%
“…The fields of ethnomathematics, critical mathematics education and, more generally, what have been known as the social, cultural and political perspectives in mathematics education have shown how mathematics is involved in processes of social selection, in excluding groups of people considered to be disadvantaged, or in providing a clear social mechanism of accountability and accreditation. A recent special issue on social theory published in this journal contemplates research where it is shown how mathematics is used as an economic measure (Tsatsaroni & Evans, 2013), a technology of subjectification (Kanes, Morgan & Tsatsaroni, in press) or as a mechanism of social selection (Jorgensen, Gates & Roper, 2013). These studies compel us to think about the importance of mathematics not in terms of object mathematicsas valuable knowledge and competencebut in terms of the role it plays and its attendant submissions to political as well as economic criteria and goals.…”
Section: Fetishism and Mathematicsmentioning
confidence: 99%
“…The specific psychometric methodology developed to measure these skills determines which aspects of adult activities are accountable and noteworthy, within a framework that postulates universal (i.e. transnational) skills (Sellar and Lingard 2014;Tsatsaroni and Evans 2013). Thus the predominant interpretations of proficiencies in the PIAAC survey within the media appear to reflect a decontextualized skills-based approach rather than one that sees them as part of situated social and cultural practices (cf.…”
mentioning
confidence: 99%
“…The TPS has mostly been addressed by critical policy studies, for analysis of global policy discourses on lifelong learning and knowledge society (Gewirtz 2008;Ball 2009), of pedagogic discourses entailed in international evaluative surveys such as the Program for International Assessment of Adult Competencies (Tsatsaroni and Evans 2014), as well as for analysis of social policy discourses for fighting poverty in Argentina and Chile (Rambla and Veger 2009) and homelessness policies in Australia (Gerrard 2015). More rarely, it has been used for analysing consequences of the implementation of such policy discourses on local agents' practices and identities (Bonal and Rambla 2003), on social relations between agents and agencies, in the field of higher education (Stavrou 2012) and ageing (Loffeier 2015).…”
Section: Developments: Pedagogisation As a Conceptual Toolmentioning
confidence: 99%